Screening urinalysis for proteinuria in school children - Partini P. Trihono; Ina S. Timan; Supriyadi Bektiwibowo; Diana Aulia; Lukman Edwar (Indonesian Pediatric Society, 2001)
Although asymptomatic proteinuria in children is uncommon, long-term follow-up of children who have persistent proteinuria reveals that they face risks to have significant glomerular changes followed by decreasing kidney function. Since 1970’s urine screening program for asymptomatic hematuria and proteinuria in schoolchildren has been conducted regularly in some countries. So far such program has never been implemented in Jakarta. As a part of The Community Health Program of the Medical School, University of Indonesia, this epidemiologic study aimed especially to look at the urine abnormalities among schoolchildren. The target population was children in grades III, IV and V of 4 elementary schools in Eastern Jakarta. Four hundred and forty nine children (217 boys and 232 girls) were enrolled in this study, held during school time in August 1999. Their mean age was 9.35 (SD 1.2) years. Data collected were history of illness, physical examination, and complete urinalysis using a dipstick method. Proteinuria was found in 30 (6.8%) children, which in repeated urinalyses were determined as orthostatic in 2 (0.4%), transient in 20 (4.5%), and persistent proteinuria in 6 (1.4%) children. Three out of 6 children with persistent proteinuria also had hematuria. One child with persistent proteinuria was considered as having urinary tract infection. We conclude that the incidence of asymptomatic proteinuria in schoolchildren is not high, but because of significant risks that they face, a long-term follow up of them is indicated.